PARENT ASSISTANCE MANAGEMENT MODEL TO IMPROVE ELEMENTARY SCHOOL STUDENTS’ LEARNING OUTCOMES IN PERCUT SEI TUAN DISTRICT - Wastuti, Sri Ngayomi Yudha; Simare-Mare, Aman; Sudirman, Sudirman (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
This study aims to develop and analyze a parental assistance management model to improve elementary school students’ learning outcomes in Percut Sei Tuan District, Deli Serdang Regency. The background of this research is grounded in the low level of parental involvement in home-based learning assistance, which has contributed to decreased student motivation and academic achievement. Through the development of a structured and collaborative parental assistance management model, this study seeks to foster synergy between schools and parents in supporting effective student learning. The study employed a mixed-methods approach with a sequential explanatory design, beginning with a quantitative phase to measure the effectiveness of parental assistance on students’ learning outcomes, followed by a qualitative phase to deepen the findings through interviews, observations, and document analysis. The research subjects included principals, teachers, and parents from several elementary schools in Percut Sei Tuan District. The findings indicate that the implementation of parental assistance designed according to the POAC management principles (Planning, Organizing, Actuating, and Controlling) has a positive effect on improving students’ learning outcomes. Quantitatively, there was an increase in students’ average academic scores and learning attitudes following the implementation of the model. Qualitatively, the results revealed improved effective communication between parents and teachers, the emergence of students’ sense of responsibility toward learning, and the creation of a more conducive home learning environment. In conclusion, this study confirms that the parental assistance management model is effective in enhancing students’ learning outcomes when implemented in a well-planned, well-coordinated manner and supported by the active involvement of schools, teachers, and parents. This model can serve as a practical guideline for elementary education institutions in building strategic partnerships between families and schools to achieve meaningful and sustainable learning.